Identification of the Learning Motivation of Class VII IT Students Al-Fahmi Palu in the 2022/2023 Academic Year - Bau Ratu; Dhevy Puswiartika; Irmawati Musa; Misnah Misnah; Herlina Herlina (Jurnal Kreatif Online, 2022)
The purpose of this study was to find out how the learning motivation of class VII students of SMP al-Fahmi, Palu city in social studies subjects. The research method used in this research is this research study using qualitative research and case study research. This study will reveal how students' learning motivation is low, high in the 2022-2023 school year. Sources of data are through survey studies on student learning motivation data when participating in the learning process, both student data for class VII SMP Al-Fahmi and teacher data through interviews on social studies (Social Sciences) subjects and through observations. The use of the instrument in this study uses interview and observation guidelines to obtain in-depth data on the implementation of this research. The data collection technique is through data triangulation and the researcher uses qualitative data analysis which is accessed through the sources proposed by Miles and Huberman and Sugiyono, namely data collection, data reduction, data presentation, and drawing conclusions. The results of this study found data that the intrinsic aspect is motivation or encouragement that arises from within students to achieve mastery of learning outcomes in class on social studies subjects